Experiences with economic reform : a review of Bangladesh's development, 1995 - Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue ; University Press Ltd., 1995)
Contributed articles.
Includes bibliographical references.
ESS, BIED
Complimentary copy from BIED (35866); Complimentary copy from Professor Dr. Nasreen Khundker (36659); Donated By Akbar Ali Khan (38674)

Donated By Rebecca Dipa Khan(42298)
Keywords: Economics; Bangladesh -- Economic policy; Bangladesh -- Economic conditions